Herring and chicken/pork meals lead to differences in plasma levels of TCA intermediates and arginine metabolites in overweight and obese men and women. Issue 3 (28th November 2016) - Vincent, Andrew; Savolainen, Otto I.; Sen, Partho; Carlsson, Nils‐Gunnar; Almgren, Annette; Lindqvist, Helen; Lind, Mads Vendelbo; Undeland, Ingrid; Sandberg, Ann‐Sofie; Ross, Alastair B.
Abstract : Replacing lean meat (chicken and pork) with herring leads to numerous metabolic changes in the blood metabolome of overweight individuals, especially around central energy and urea metabolism. Changes suggest that nitric oxide (NO) production is affected, and it is confirmed that herring increases NO production in men. This suggests a new way in which fish may protect against cardiovascular disease. Abstract : Scope: What effect does replacing chicken or pork with herring as the main dietary source of protein have on the human plasma metabolome? Method and results: A randomised crossover trial with 15 healthy obese men and women (age 24–70 years). Subjects were randomly assigned to four weeks of herring diet or a reference diet of chicken and lean pork, five meals per week, followed by a washout and the other intervention arm. Fasting blood serum metabolites were analysed at 0, 2 and 4 weeks for eleven subjects with available samples, using GC‐MS based metabolomics. The herring diet decreased plasma citrate, fumarate, isocitrate, glycolate, oxalate, agmatine and methyhistidine and increased asparagine, ornithine, glutamine and the hexosamine glucosamine. Modelling found that the tricarboxylic acid cycle, glyoxylate, and arginine metabolism were affected by the intervention. The effect on arginine metabolism was supported by an increase in blood nitric oxide in males on the herring diet. Conclusion: The results suggest that eating herring instead of chicken and lean pork leads to important metabolic effects, particularly on energy and amino acid metabolism. Our findings support the hypothesis that there are metabolic effects of herring intake unrelated to the long chain n‐3 polyunsaturated fatty acid content.